MoCA Test: Validation of a five‐minute telephone version. (31st December 2021) - Nasreddine, Ziad S
Abstract: Importance: This study validates the use of a telephone version of the MoCA Test, which helps health professionals assess patients remotely. Objectives: This is a validation study for a 5 minute telephone version of the MoCA. Study design: The subjects' performances were compared to results obtained from the full version of the MoCA test, at an average of 50.8 days, prior to having completed the 5 Min Telephone MoCA. Participants: 84 consecutive subjects were approached to participate in the study. Subjects had to be over 50, male or female, an education level of 6 years. Settings: Subjects were recruited in a memory clinic setting. Outcomes and Measures: Correct classification and correlation between the Telephone MoCA and full MoCA was evaluated, with area under the curve (AUC) analysis, and Pearson Coefficient respectively. Results: 81 subjects were recruited, and 3 subjects declined participation. The average age of the subjects was 69 (Range 47‐92) with a sex distribution of 42 females and 41 males. The average education level for the subjects was 12.6 years. The 5 Min Telephone MoCA results correlated well with the full version of the MoCA, with an area under the curve of 0.864 and a strong Pearson Coefficient of 0.74. Conclusion and Relevance: The 5 Min Telephone MoCA is feasible, practical, and reliable, when compared to the full, in‐clinic, MoCA. Clinicians are already familiar with the use of the full MoCA Test, and this new 5 min telephone version, can help them reliably assess patients who cannot make to an in clinic evaluation.